1995
DOI: 10.1097/00003246-199511000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gut intramucosal pH and gut oxygen extraction ratio in a porcine model of peritonitis and hemorrhage

Abstract: Since a reduction in blood flow was preceded by a decrease in intramucosal pH, low intramucosal pH in peritonitis cannot be explained by low flow alone. Gut oxygen delivery proved to be a poor indicator of gut acidosis (i.e., low intramucosal pH). In peritonitis, a decreasing intramucosal pH was associated with an increasing oxygen extraction ratio. In hemorrhage, this association had a sharp deflection point below which a further decrease in intramucosal pH occurred concomitantly with an unchanged gut oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Theisen et al (39) reported alterations in microvascular blood flow to the gut mucosa in a porcine model of hyperdynamic endotoxic shock (ES). Gut alterations, including ileal mucosal acidosis (3), increase in mucosal permeability (31), and gut ischemia (15), have often been reported after administration of lipopolysaccharide (LPS) or live bacteria. Clinical and laboratory research indicates that gut ischemia may be a pivotal initiating event in the secretion of numerous proinflammatory mediators that causes multiple organ failure (14).…”
mentioning
confidence: 99%
“…Theisen et al (39) reported alterations in microvascular blood flow to the gut mucosa in a porcine model of hyperdynamic endotoxic shock (ES). Gut alterations, including ileal mucosal acidosis (3), increase in mucosal permeability (31), and gut ischemia (15), have often been reported after administration of lipopolysaccharide (LPS) or live bacteria. Clinical and laboratory research indicates that gut ischemia may be a pivotal initiating event in the secretion of numerous proinflammatory mediators that causes multiple organ failure (14).…”
mentioning
confidence: 99%
“…Experimental studies have shown that supply-dependent oxygen consumption develops at a pHi of 7·1, and below this level an anaerobic metabolism prevails 14 . Clinical studies have suggested that this threshold is associated with colonic ischaemia and major complications 5,7 -9 .…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19][20] It has been also shown, by several different techniques, that decreases in blood flow to the gut are paralleled by concordant decreases in pHi and increases in tissue PCO 2 determined by tonometry.…”
Section: The Tonometric Methodsmentioning
confidence: 99%